Preparation of nano-SIO2/NR composites with deposition method - Tongjian Zhao; Jiang Wang; Xin Fu (Proceedings of IRRDB Conference: NR Industry: Responding to Globalization, 7-8 September 2004, Kunming International Convention & Exhibition Center, China. pp.497-503.)
This article adopts the new technics method of deposition to prepare Nano-SiO2, investigation on Na2SiO3 9H2O is made to Nano-SiO2 latex in reaction of the hydrochloric acid with assistants and then mixes with Natural latex to prepare the Nano-SiO2/NR composites. Changing the concentration of Na2SiO3 9H2O, temperature and time of reaction to control the size and distributing of Nano-particle. According to the property of composites and the design of orthogonal experiments to get the best conditions. Results indicate: the concentration of Na2SiO3 9H2O is 190g . 1 -1, the time is (1) 30min, (2) 45min, temperature is 90 oC; the tensile strength of the Nano-SiO2/NR composites prepared by the method get to 29.05MPa, avulsion strength to 56.88 kN/m, property get more increase. And according to the modern technique of SEM, STM, DMA and so on, to analyze Nano-configuration and the mechanism of surfaces. Experiment shows that the technical property of Nano-SiO2/NR composites made by this method are very good.
Keywords: Composites; Nano-SiO2; NR; Preparing technics